Epidemiology of loneliness & social isolation, an emerging public mental health predicament in India: a scoping review - Niranjan Muralikrishnan; Sendilkumar Balasundaram (Discover Mental Health)
Abstract Background Loneliness and Social Isolation (SI) has evolved into an epidemic and WHO has alarmed many developed and developing countries that their citizens are going through the epidemic of loneliness and SI. It affects the Mental Health status of a person & leads to morbidities and premature death. Loneliness and SI are overlooked subjects resulting in poor research turnover. This scoping review has explored the extent of literature availability on loneliness and SI in India Objective To evaluate the availability of literature on loneliness and SI in India Methods A scoping review was conducted using predetermined search terms in Google Scholar and PubMed, selecting only open-access articles. Selected articles were scrutinized for their quality with the help of STROBE & COREQ checklists before entering into the review Results A total of 155 articles were screened and after excluding the duplicates129 articles were chosen for the next step to screen for inclusion criteria and finally nine articles were selected for this review. The highest prevalence of loneliness and SI reported was 37.6% and the lowest was 18.3% Conclusion There is a lack of literature on loneliness and such available kinds of literature are done among the geriatric population only. The scientific community should focus on this emerging domain and come out with true prevalence rates among different age groups so that effective strategies can be devised to address this latent yet significant mental health issue in India.